EDIBLE COATING DENGAN KONSENTRASI PATI JAGUNG PADA TOMAT SELAMA PENYIMPANAN - Wendra Mardayansa; Faizah Hamzah; Yossie Kharisma Dewi (Fakultas Pertanian Universitas Riau, 2025)
Tomatoes were classified as climacteric fruit with a hightwater content of up to 94%, which caused them to spoil quickly. The method used to extend the shelf life and inhibit spoilage was the application of an edible coating. This research aimed to determine the best concentration of corn starch in the production of edible coating on tomatoes during storage. The study was carried out experimentally using a Complete Randomized Design (RAL). The treatments in this study were the addition of corn starch concentrations, namely P1(control), P2(corn starch concentration 1%), P3(corn starch concentration 2%), P4(corn starch concentration 3%), P5(corn starch concentration 4%), and P6(corn starch concentration 5%). The observed parameters included weight loss, total dissolved solids, vitamin C, hardness, and color. The data were analyzed statistically using analysis of variance (ANOVA) and if the F count ≥ F table then further testing carried out with Duncan's Multiple Range Test (DMRT) at the 5% significant level. The best treatment in this study was obtained at P6with a concentration of 5%. This treatment gave produce weight loss 7.93%, total dissolved solids 1.65°Brix, vitamin C 21.63 mg/100 g, hardness 3.53 kg/f, color basen on L 35.12 (lightness), color basen on a* 24.98 (redness), color basen on b* 2.37 (yellowness).